2014
DOI: 10.1007/s11468-014-9835-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Optical Transmission Spectra of Plasmonic Spherical Nano-Hole Arrays

Abstract: Plasmonic nano-structures are important for many photonic devices and applications. The optical transmission spectra of such structures are extraordinary. In this paper, we investigate the optical transmission spectra of thin gold films perforated with imperfect circular nano-hole arrays using the finite difference time domain (FDTD). It is observed that both of the intensity and resonance positions of the transmission spectra of perfect plasmonic circular nano-hole arrays are strongly modified due to nano-hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Both methods have been widely used to simulate the optical properties of artificial subwavelength nanostructures and are in good agreement with the experiment [42][43][44]. In addition to the bionic moth eye structure, researchers have designed a series of artificial nanostructures with good antireflection effects, including nanowires [45,46], nanocones [47,48], nanoholes [49,50], nanopyramids [51,52], and some complex composite structures [53,54]. Micronanomanufacturing technology is the key to realizing that artificial antireflection nanostructures can be applied to silicon solar cells.…”
Section: Introductionmentioning
confidence: 74%
“…Both methods have been widely used to simulate the optical properties of artificial subwavelength nanostructures and are in good agreement with the experiment [42][43][44]. In addition to the bionic moth eye structure, researchers have designed a series of artificial nanostructures with good antireflection effects, including nanowires [45,46], nanocones [47,48], nanoholes [49,50], nanopyramids [51,52], and some complex composite structures [53,54]. Micronanomanufacturing technology is the key to realizing that artificial antireflection nanostructures can be applied to silicon solar cells.…”
Section: Introductionmentioning
confidence: 74%
“…Plasmonic metamaterials have been recently recognized as a new border of engineering since the discovery of their confinement of optical field [11][12][13]. It has been found that the plasmonic effect induced by metamaterial absorbers is a promising approach to achieve Materials 2021, 14, 1380 2 of 11 light trapping in thin-film solar cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…The motivating optical properties are determined by the localized and propagating surface Plasmon resonances (SPR). These Plasmonic resonances of the metal surfaces can be adapted by proper tuning of the physical and geometrical parameters of such structures [11,12].Because of these benefits the surface Plasmon resonance-based optical fiber sensors have drawn a lot of attention [13][14][15][16][17][18].For LSPR sensor various type of metals like silver, copper and aluminium used at the surface near sensing layer to excite these waves. Pradeep Kumar Teotia et al [19] obtained high sensitivity using multilayer grating configuration.…”
Section: Introductionmentioning
confidence: 99%